Medullary vasomotor center: a modern view of the structure, function and its role in arterial hypertension pathogenesis - Danukalo, M.; Hancheva, O.; Melnikova, O.; Isachenko, M. (Journal of Education, Health and Sport, 2021)
The medullary centers of blood pressure regulation have been in the field of vision of both physiologists and doctors for a very long period of time. This is mainly due to the abundance of structures and interstructural interactions in the brain stem, involved in maintaining blood pressure. Advances in research technology open new opportunities these days to look at this problem from a different angle. Moreover, research of medullary centers of blood pressure regulation will make it possible to understand better the mechanisms of persistent increase in blood pressure, which will create the preconditions for the formation of new pathogenetically substantiated therapeutic approaches in the treatment of such a widespread and dangerous pathology as arterial hypertension. Therefore, the aim of this work was to analyze modern views about the structure and composition of the medullary vasomotor center, its functions and its role in the arterial hypertension development. To achieve this goal, the search by keywords: arterial hypertension, baroreflex, NTS, DMN, RVLM, CVLM, CPA, SHR, LC and analysis of scientific articles from the databases of search engines Google Scholar, Web of Science, Pub Med was done. Conclusions: 1. The analysis of literature sources showed that the concept of "medullar vasomotor center" includes a number of brainstem formations, the most studied of which are the structures of the dorsal complex of the vagus nerve (the nucleus of the solitary tract, the dorsal motor nucleus, area postrema), the rostral and caudal ventrolateral regions of medulla, caudal pressor area, noradrenergic structures of the brainstem, in particular the locus coeruleus, as the biggest of them. 2. According to literary sources, arterial hypertension is accompanied by the changes in the morphofunctional state of the above-mentioned structures. The most common mechanisms are violation of the neurotransmitter composition within the structure and the neuroinflammatory process.